Implikasi Penunjukan Desa Adat Sebagai Subyek Hak Atas Tanah Terhadap Eksistensi Tanah Adat (Study Pada Desa Pejeng Kelod Kabupaten Gianyar) - I Wayan Wiasta; I Wayan Eka Arta Jaya; Luh Gede Lilis Widyasanthi (Jurnal Ilmiah Raad Kertha, 2020)
The customary land in Bali is known as the Druwe Desa land which is under the authority of the adat village. Traditional village is a term used to refer to religious social institutions that oversee the unity of indigenous and tribal peoples that exist in every village in Bali. Customary villages have the right to autonomy from traditional law to regulate their own households, known as awig-awig. With the promulgation of Bali Provincial Regulation Number 4 of 2019 concerning Customary Villages in Bali further strengthens the existence, functions and duties of traditional villages. So that customary villages are recognized as legal subjects to ownership of land rights. So that customary land in Bali can be registered as communal property rights based on the Decree of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 276/KEP-19.2/X/ 2017 through Complete Systematic Land Registration in order to guarantee legal certainty. But in fact, there is a concern about the transfer of rights so that it affects the existence of customary land. The specific purpose of this study is to analyze the implications and strategies in maintaining the existence of customary land in the village of Pejeng Kelod. The strategy of maintaining the existence of customary land itself is strengthened by awig-awig and forming a good governance system